2018
DOI: 10.1111/psyp.13198
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in decisiveness: ERP correlates of response inhibition and error monitoring

Abstract: The aim of the current study was to examine whether and how self-reported decisiveness is associated with response inhibition and performance monitoring. We hypothesized that these two cognitive control mechanisms, both of which are often associated with decision making, would differ in individuals varying in decisiveness. We focused on ERP correlates and behavioral measures of inhibition and error processing in the stop-signal task. We expected a negative relationship between decisiveness and behavioral measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 93 publications
(160 reference statements)
2
5
0
Order By: Relevance
“…In the present study, a pronounced P3 was elicited by lowfrequency stop-signal trials of both successful and unsuccessful inhibition, which is consistent with the context-updating hypothesis for the P3 (Donchin & Coles, 2010). Moreover, the stop-P3 was enhanced for successful relative to unsuccessful inhibition over central areas, which is in line with numerous previous studies (de Jong, Coles, Logan, & Gratton, 1990;Dimoska et al, 2003;Greenhouse & Wessel, 2013;Overtoom et al, 2002;Schevernels et al, 2015;Senderecka, 2016;Senderecka, Szewczyk, Wichary, & Kossowska, 2018;Shen, Lee, & Chen, 2014;Smith & Mattick, 2013) and supports the view that the stop-P3 is associated with inhibitory processing and the success of inhibition . Importantly, no group differences were found for the stop-P3 across successful and unsuccessful trials.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, a pronounced P3 was elicited by lowfrequency stop-signal trials of both successful and unsuccessful inhibition, which is consistent with the context-updating hypothesis for the P3 (Donchin & Coles, 2010). Moreover, the stop-P3 was enhanced for successful relative to unsuccessful inhibition over central areas, which is in line with numerous previous studies (de Jong, Coles, Logan, & Gratton, 1990;Dimoska et al, 2003;Greenhouse & Wessel, 2013;Overtoom et al, 2002;Schevernels et al, 2015;Senderecka, 2016;Senderecka, Szewczyk, Wichary, & Kossowska, 2018;Shen, Lee, & Chen, 2014;Smith & Mattick, 2013) and supports the view that the stop-P3 is associated with inhibitory processing and the success of inhibition . Importantly, no group differences were found for the stop-P3 across successful and unsuccessful trials.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, neural processing of the errors is modulated by individual differences as subjective factors. Several studies have reported that error-related brain responses are enhanced by various individual differences [e.g., decisiveness (Senderecka et al, 2018), conscientiousness (Pailing and Segalowitz, 2004), socialization (Dikman and Allen, 2000), and agreeableness (Tops et al, 2006)]. The present study showed the novel findings that error-related brain responses are changed not only by the individual differences due to subjective factors but also by the temporal fluctuations of the mood for the upcoming outcome of the task.…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, individuals high (vs. low) in NFC exhibit attenuated sensitivity to cues for response adjustment and decreased sensitivity to committing errors, manifesting as lower N2 response to stimulus-response congruency and smaller ERN responses, respectively (Kossowska, Czarnek, Wronka, Wyczesany, & Bukowski, 2014). Similarly, decisiveness as a key facet of NFC is linked to worse performance in the stop-signal tasks, in parallel with lower N1 and P3 responses to stop signals as well as decreased ERN amplitudes to error responses (Senderecka et al, 2018). On the other hand, a growing body of evidence has indicated that high (vs. low) NFC individuals perform better in the tasks involving selective attention, suggesting that NFC is associated with efficient selection of relevant information from the environment (Kossowska, 2007a(Kossowska, , 2007b.…”
Section: Discussionmentioning
confidence: 99%